Simulated Night-Shift Schedule Disrupts the Plasma Lipidome and Reveals Early Markers of Cardiovascular Disease Risk [Corrigendum] - Kyle JE; Bramer LM; Claborne D; Stratton KG; Bloodsworth KJ; Teeguarden JG; Gaddameedhi S; Metz TO; Van Dongen HPA (Nature and Science of Sleep, 2023)
Kyle JE, Bramer LM, Claborne D, et al. Nat Sci Sleep. 2022;14:981–994. The authors have advised there is an error in Figure 1 on page 983 of the published paper. Due to an error that occurred inadvertently at the time of figure assembly the nighttime meals in the simulated night shift condition – which occurred at 01:00 after 7.0 hours of scheduled wakefulness on days 3, 4 and 5 – were missed in the schematic. The correct Figure 1 is as follows.